Long-term stability of NH3-SCR catalysts in the presence of high NO2 concentrations and the performance of a modified V-W-Mo catalyst - Bo Yu; Qichao Li; Shuran Zhou; Heng Yang; Xingyu Liu; Hanjun Lu; Zhongwei Wang; Li Yang; Fang Liu (Fuel, 2027)

Distributions and controls of carbonate parameters in offshore oil and gas fields of the Beibu Gulf and adjacent northern South China Sea (nSCS) shelf during the fall season - Hanjun Yin; Wei Yang; Minxia Zhang; Xiaojuan Peng; Hong Tang; Jianjun Ye; Chuqian Lu (Marine Environmental Research, 2026)

Csp-π-d conjugation engineering strategy for optimizing *OH intermediate regulation of reinforced oxygen reduction reaction - Yang Lu; Yimin Mou; Ziyang Jia; Yiyi Fan; Lei Cheng; Yawen Tang; Yafei Li; Yu Wang; Hanjun Sun (Science Bulletin, 2026)

Synthesis and mechanistic insights of α-chlorinated lauric acid as a high-efficiency collector for apatite flotation - Wenda Guo; Heng Zhang; Zhenyue Zhang; Haolong Lu; Defeng Liu; Hanjun Wu (Minerals Engineering, 2026)

Nitrogen-doped porous biomass-derived carbons for enhanced hydrophobicity, microwave absorption and thermal insulation - Siyu Chen; Zhiyong Chen; Lu Tang; Jimei Xue; Zhijun Wang; Ying Li; Hanjun Wei (Fuel, 2026)

Highly active and selective sandwich-like SiO2@Cu-Fe@H-SiO2 catalysts for CO2 upgrading via reverse water-gas shift: The effect of Fe doping position - Xiaoyu Liang; Feng Yan; Hanjun Liu; Feng Xie; Yixuan Lu; Linying Huang; Xuehua Shen; Zuotai Zhang (Journal of Environmental Chemical Engineering, 2025)

Full-spectrum-responsive Ti4O7-PVA nanocomposite hydrogel with ultrahigh evaporation rate for efficient solar steam generation - Xinye Xu; Qi Zhao; Qi Liu; Junxiao Qiu; Jinhao Li; Wenqian Zheng; Jie Cao; Lina Wang; Wen Wang; Shutong Yuan; Anni Fu; Hanjun Yang; et al. (Desalination, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)